-2, -2, -2, +2
-2 + -2 + -2 + 2
-2 -2 -2 + 2
-6 + 2
-4
-4/ 4 = -1
His average is -1
I believe the answer to this is correct and i believe he did this by adding(i think)
Answer:
b. 4x^2 + 3x - 6
Step-by-step explanation:
The values of f(x) for the extremes of x are more positive than the value of f(x) for the middle x, so we know the parabola opens upward. That eliminates choice D.
It is probably easiest to evaluate the other expressions to see which one matches the given f(x) values. For the purpose, it is usually easier to use the Horner form of the equation.
a. f(-2) = (3(-2) +4)(-2) -6 = -2(-2) -6 = -2 ≠ 4
b. f(-2) = (4(-2) +3)(-2) -6 = -5(-2) -6 = 4 . . . . matches the given data point
c. Because (b) matches, we know this one will not.
The appropriate choice is B.
Answer:
i dont understand
Step-by-step explanation: